The Influence of Brand Image, Service Quality and Word of Mouth on Students' Decision in Choosing Tuition Classes - Fitrinada, Dela Masita; Santoso, Budi; Anita, Sumarni Bayu (Jurnal Pewarta Indonesia, 2024)
The research set out to analyze the impact of brand image, service quality, and word of mouth on Class 12 students' course selection at Bimbingan Tes Alumni (BTA) in Palembang. Employing a quantitative survey approach, the study included 152 class 12 students enrolled at the branch. The findings revealed that service quality and word of mouth significantly influenced students' course decisions. Notably, superior service quality heightened student satisfaction and loyalty, while word of mouth substantially shaped student choices. Conversely, brand image did not emerge as a significant factor in course selection. These results indicate that Bimbingan Tes Alumni (BTA) in Palembang should prioritize enhancing service quality to foster positive word of mouth and attract new students. Although brand image had less impact, maintaining a strong brand image remains integral to a comprehensive marketing strategy.